Grit [compact disc, unabridged] : the power of passion and perseverance - Duckworth, Angela (Audioworks, an imprint of Simon & Schuster Audio Division, 2016)
Why do some people succeed and others fail? Sharing new insights from her landmark research on grit, MacArthur genius Angela Duckworth explains why talent is hardly a guarantor of success. Rather, other factors can be even more crucial such as identifying passions and following through on commitments. Drawing on her own powerful story as the daughter of a scientist who frequently bemoaned her lack of smarts, Duckworth describes her winding path through teaching, business consulting, and neuroscience, which led to the hypothesis that what really drives success is not genius but a special blend of passion and long-term perseverance. As a professor at the University of Pennsylvania, Duckworth created her own character lab and set out to test her theory.